Molecular dynamics simulation of oxygen ion diffusion in yttria stabilized zirconia single crystals and bicrystals - Huang, H. C. (2014)
Molecular dynamics simulation studies have been performed to study the oxygen ion diffusion in yttria stabilized zirconia single crystals and bicrystals separated by tilt grain boundaries (GBs). Two types of GBs which are Σ 5 (3 1 0) and Σ 13 (5 1 0) are studied at temperatures between 1,000 K and 2,000 K. The effect of grain size, which is the distance between two GBs, and the effect of GB orientations are systematically investigated in this study. The oxygen diffusion in the bicrystals is found to be blocked by the GB, and the blocking effect increases with decreasing grain size and is affected by different grain orientations. In addition, the oxygen diffusion along the GB plane is most hindered.